Do the high-tech industrial development zones foster urban innovation?: A case study of China - Wang, Qixuan; Ren, Jie; Yan, Simin; Cao, Zhan; Cheng, Yao (Land, 2023)
China’s high-tech industrial development zones (HIDZs) is a key “place-based” policy targeting national innovation-driven development. Despite the extensive research on HIDZs, it remains unclear whether and to what extent the policy has fostered cities’ innovation output and quality. Basing our research on panel data of Chinese cities from 2001 to 2019, we employed the PSM-DID model to examine the impact of HIDZs policy on their host cities’ innovation output and quality. The empirical results show that: (1) In general, the establishment of HIDZs has a more significant positive effect on fostering urban innovation output compared to its role in promoting urban innovation quality. However, (2) the effect on urban innovation output and quality varies across different cities. For cities with more advantageous locations and policies, HIDZ policy plays a more instrumental role in promoting the quality of urban innovation, while the establishment of HIDZs in other cities is more conducive to increasing the output of urban innovation. Ultimately, we argue that authorities must recognize the importance of integrated development of HIDZs and their host cities and incorporating HIDZs’ impact on the host cities into the HIDZ evaluation. It is necessary to understand that HIDZs have multiple development modes due to their specific local conditions. Hence, differentiated guidance must be carried out rather than directly replicating the experience from developed regions.
Gesehen am 21.09.2023